Evaluating the Validity, Reliability and Authenticity of English Achievement Test for the Twelfth Grade Students of SMAN 4 Tebo, Jambi - Winarti, Muncar; Faridi, Abdurrachman; Rozi, Fahrur (English Education Journal, 2021)
This study aims to investigate the implementation of the English achievement test for the twelfth-grade students at SMAN 4 Tebo, Jambi in the academic year 2019/2020. This study was a contenr analyis. The objects of this study were English achievement test items. It consisted of 40 multiple-choice questions and 5 essay questions. The data collection method was a document analysis checklist. In this study, the researcher analyzed the data from English achievement test for validity aspects such as content validity and construct validity, the degree of reliability, and the implementation of language authenticity criteria. The findings of this study revealed that; (1) the content validity shows 76% valid, and the construct validity shows 60% valid; (2) the reliability shows coefficient 0.281 for multiple-choice items and 0,554 for essay items, and it is reliable; (3) the results of analyzing the authenticity shows that the listening items, reading test and essay writing are authentic. However, each part has some weaknesses. Especially in the reading test, most of the passages use in reading tests failed to represent the world context even though the topics of the passages are rational and based on the real context. Nevertheless, the English teacher who constructed the English achievement test did not mention the sources from which the passages were taken. Next, the samples of the format letter, announcement, and pamphlet look unnatural view from the format and design. Moreover, the English Achievement Test for twelfth-grade students of SMAN 4 Tebo, Jambi has fulfilled the characteristics of validity, reliability, and authenticity as a good test or standardized test.